Effects of a short daytime nap on shooting and sprint performance in high-level adolescent athletes - Suppiah, H. T.; Low, C. Y.; Choong, G.; Chia, M. (International Journal of Sports Physiology and Performance, 2019)
Purpose: To investigate the sport-specific performance effect of a brief afternoon nap on high-level Asian adolescent student-athletes who were habitually short sleepers. Methods: Participants were randomly assigned to a nap or nonnap (reading) condition. In the first study, 12 male shooters (13.8 [1.0] y) performed a shooting assessment (20 competition shots) with heart-rate variability monitored during the assessment. In the second study, 19 male track-and-field athletes (14.8 [1.1] y) performed a 20-m sprint-performance assessment. Subjective measures of sleepiness and alertness were obtained in both studies. Results: The brief nap had no effect on any measure of shooting performance (P>.05) or autonomic function (P>.05) in shooters. However, the fastest 20-m sprint times increased significantly (P<.05) from 3.385 (0.128) s to 3.411 (0.143) s, with mean 2-m times trending toward significance (P<.1) among the track-and-field athletes. No significant differences were observed in any other measures. Conclusions: The results of the research indicate varying effects of naps between sport-specific performance measures. Napping had no effect on shooting performance, whereas a negative effect existed in 20-m sprint performance, potentially due to sleep inertia. Considering these findings, some caution is warranted when advocating naps for adolescent athletes.